2012
DOI: 10.1182/blood-2011-08-373944
|View full text |Cite
|
Sign up to set email alerts
|

The C-type lectin receptor CLEC9A mediates antigen uptake and (cross-)presentation by human blood BDCA3+ myeloid dendritic cells

Abstract: CLEC9A is a recently discovered C-type lectin receptor involved in sensing necrotic cells. In humans, this receptor is selectively expressed by BDCA3 ؉ myeloid dendritic cells (mDCs), which have been proposed to be the main human cross-presenting mDCs and may represent the human homologue of murine CD8 ؉ DCs. In mice, it was demonstrated that antigens delivered with antibodies to CLEC9A are presented by CD8 ؉ DCs to both CD4 ؉ and CD8 ؉ T cells and induce antitumor immunity in a melanoma model. Here we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
181
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(188 citation statements)
references
References 50 publications
4
181
1
1
Order By: Relevance
“…This result is in keeping with a recent study demonstrating that human blood BDCA3 1 DCs stimulated with Poly(I : C) produce only low levels of IL-12p70. 54 Furthermore, a recent study on in vitro derived CD141 1 CLEC9A 1 DCs differentiated from HSCs in the presence of a cocktail of cytokines including SCF, Flt3L, IL-3, IL-6, GM-SCF and IL-4 has shown a similar poor response of this population to TLR stimulation with respect to IL-12p70 production. 23 They demonstrated that a further stimulus of antigenspecific T cells was required to produce IL-12p70.…”
Section: Discussionmentioning
confidence: 98%
“…This result is in keeping with a recent study demonstrating that human blood BDCA3 1 DCs stimulated with Poly(I : C) produce only low levels of IL-12p70. 54 Furthermore, a recent study on in vitro derived CD141 1 CLEC9A 1 DCs differentiated from HSCs in the presence of a cocktail of cytokines including SCF, Flt3L, IL-3, IL-6, GM-SCF and IL-4 has shown a similar poor response of this population to TLR stimulation with respect to IL-12p70 production. 23 They demonstrated that a further stimulus of antigenspecific T cells was required to produce IL-12p70.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12] Human BDCA-3 ϩ DCs internalize dead cell material and crosspresent exogenous soluble or cell-associated proteins to CD8 ϩ T cells. [11][12][13] Recombinant soluble HCMV pp65 antigen was crosspresented with increased efficiency by BDCA-3 ϩ DCs to antigenspecific CD8 ϩ T cells. 12 For vaccination strategies, full grasp on the uptake and processing mechanisms and preferentially a further increase in CD8 ϩ T-cell stimulation potency is desired, which was the aim of our study.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, uptake and cross-presentation of soluble Ag is mediated by the mannose receptor (MR) in in vitro BM-derived DCs, whilst this process is independent of MR in splenic CD8α + and CD11b + DCs [20]. In humans, MoDCs express high levels of MR whereas CD1c + DCs and CD141 + DCs express little if any MR [21,22], which may account for the lower uptake of soluble protein by CD1c + DCs and CD141 + DCs and suggests that similar uptake mechanisms occur between species. Consistent with their known higher levels of lysosomal proteases [22,23] the proteasome for processing of the pp65 NLV epitope, suggesting preferential use of the vacuolar pathway by MoDCs.…”
Section: Discussionmentioning
confidence: 99%